High Levels of Viral Replication Contrast with Only Transient Changes in CD4(+) and CD8(+) Cell Numbers during the Early Phase of Experimental Infection with Simian Immunodeficiency Virus SIVmnd-1 in Mandrillus sphinx - Onanga, Richard (American Society for Microbiology, 2002)
Early events during human immunodeficiency virus infections are considered to reflect the capacity of the host to control infection. We have studied early virus and host parameters during the early phase of simian immunodeficiency virus SIVmnd-1 nonpathogenic infection in its natural host, Mandrillus sphinx. Four mandrills were experimentally infected with a primary SIVmnd-1 strain derived from a naturally infected mandrill. Two noninfected control animals were monitored in parallel. Blood and lymph nodes were collected at three time points before infection, twice a week during the first month, and at days 60, 180, and 360 postinfection (p.i.). Anti-SIVmnd-1 antibodies were detected starting from days 28 to 32 p.i. Neither elevated temperature nor increased lymph node size were observed. The viral load in plasma peaked between days 7 to 10 p.i. (2 × 10(6) to 2 × 10(8) RNA equivalents/ml). Viremia then decreased 10- to 1,000-fold, reaching the viral set point between days 30 to 60 p.i. The levels during the chronic phase of infection were similar to that in the naturally infected donor mandrill (2 × 10(5) RNA equivalents/ml). The CD4(+) cell numbers and percentages in blood and lymph nodes decreased slightly (<10%) during primary infection, and CD8(+) cell numbers increased transiently. All values returned to preinfection infection levels by day 30 p.i. CD8(+) cell numbers or percentages, in peripheral blood and lymph nodes, did not increase during the 1 year of follow-up. In conclusion, SIVmnd-1 has the capacity for rapid and extensive replication in mandrills. Despite high levels of viremia, CD4(+) and CD8(+) cell numbers remained stable in the post-acute phase of infection, raising questions regarding the susceptibility of mandrill T cells to activation and/or cell death in response to SIVmnd-1 infection in vivo.